Aliran-Aliran dalam Pendidikan: Perspektif Filsafat - RAMDANI , FALIKHAH; MILLAH , DHIYAUL; HILMIYAH, FARIDATUL; INDRIANA, DINA; HIDAYAT, WAHYU (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This study examines several schools of education from a philosophical perspective. Through thorough research, this study identifies and explains the essence of educational schools such as essentialism, progressivism, reconstructionism, humanism, existentialism, conservatism, religious rationalism, and pragmatism. The authors present a detailed comparison of different educational approaches. The study also explores the impact of different philosophies of different schools on learning, teaching, and curriculum development. Therefore, the aim of this study is to provide a global image of educational dynamics.